Recursive correlation between voluntary disclosure, cost of capital, information asymmetry, and firm value - Yossi Diantimala; Sofyan Syahnur; Islahuddin Islahuddin (Cogent Business & Management, 2022)
This study examines the impact of voluntary disclosure on the cost of capital and information asymmetry, and thereby on firm value in a comprehensively recursive model. We argue that there is unidirectional dependency among the information asymmetry, cost of capital, and such firm value, hence, for any given value of voluntary disclosure, values for information asymmetry, cost of capital, and firm value can be determined sequentially rather than jointly. A sample of 1920 companies-years of non-financial companies listed on the Indonesia Stock Exchange from 2012 to 2019 is employed. The data used are a voluntary disclosure index obtained by using a self-constructed index. To calculate the cost of capital, stock market data in the form of closing prices, bid and ask prices, and some outstanding shares, as well as company financial data, are used. In examining the hypothesis, the recursive path model is utilized. The results show that the negatively direct effect of disclosure on information asymmetry and cost of capital is consistent with the hypothesis. The indirect effect of disclosure on firm value through information asymmetry is also relevant to the hypothesis. The findings suggest that higher disclosure provides great benefits for the companies as well as investors and lenders. Increasing disclosure reduces information asymmetry and the cost of capital, thereby increasing firm value.
Keywords: 650; information asymmetry; firm value; cost of capital; recursive correlation; voluntary disclosure